New Publications (Journal of Political Economy, 1907)
Agricultural Statistics, 1906. Vol. XLI, Part II. Returns of Produce of Crops in Great Britain, with Summaries for the United Kingdom. London: Wyman. Pp. 76. 55. Albert, R. A., and Schmekel, M. Der Boden u. die landwirtschaftl. Verhaltnisse des Preussischen Staates. 7. Bd. Berlin: Paul Parey, 1906. M.10 Alessandri, P. E. Merceologia tecnica. Materie prime greggie e semi-lavorate di uso commerciale ed industriale. Milano, 1907. 8vo, pp. xi + 530. L. 6 Alkoholismus, Der. Seine Wirkungen und seine Bekampfung (Aus Naturu. Geisteswelt. Bd. 145). Leipzig: Teubner, 1907. M. 1. Annuaire de 1'administration des con? tributions indirectes. Situation au ier